FACTORS INFLUENCING THE INCIDENCE OF PRE-ECLAMPSIA IN PREGNANT WOMEN IN JEMBER DISTRICT - Kholifah, Siti; Permatasari, Elok; Endah Yani, Ristya Widi (Quality: Jurnal Kesehatan, 2025)
Background: Pre eclampsia is a pregnancy complication characterized by high blood pressure that the sistole and diastole exceed 140/90 mm/Hg and protein in the urine (>300 mg/24 hours). Edema (Edema refers to swelling caused by excess fluid trapped in the body's tissues) develops during the 20 weeks of pregnancy until the last day of a week postpartum. This condition is  one of the causes of maternal death in the world, including in Indonesia.Method: This research is an analytical observational quantitative research with a cross-sectional approach.Result: Based on the logistic regression test it is concluded that the main factor of the occurrence of pre-eclampsia in pregnant women in Jember are : utilization of health services, consumes of highblood pressure drugs and blood boosting tablet,phisycal activities, health services acces, ANC complience, adequate social support and health care with  p value < 0.005.Conclusion: Pregant women’s knowledge influences their behavior, a proper education and guidance for health checks before and during pregnancy must be given, a support is necessary wether from husband, family and friends, medical team has a very important role in assisting and taking care of mothers and babbies health.